Relationship of Nurses to the Level of Knowledge about Basic Trauma Cardiac Life Support in Handling of Primary Survey - Andi Bintang; Sumarni Sumarni (Indonesian Journal of Global Health Research, 2022)
The Emergency Room (IGD) is included in the service unit in a hospital, where the emergency room is a place in a hospital that has a work team with special abilities and equipment, which provides emergency services. The aim of this research is to know the relationship between level of knowledge of nurses about BTCLS (Basic Trauma Cardiac Life Support) with the handling of the Primary Survey in the emergency department. Theresearch conducted in the emergency departement General Hospital tourism university of East Indonesia in West Sulawesi Selatan. The research used the quantitative with a correlative analytic, using cross sectional design. The samples of the research used a total sampling technique of sixteen respondents. The data of the research were analyzed by using the statistical analysis of Chi Square. The result of the research shows that 50% of the nurses have a good knowledge category with skilled Primary. Survey handling, and the rest 50% have a less knowledge category with skilled Primary Survey handling. The value of p is 0,046 which is smaller than 0,05. This indicates that Ha is verifed meaning that there is not any correlationbetween the nurses’ level of knowledge on BTCLS with the handling of the Primary Survey. The level of nurses knowledge about BTCLS is related to the handling of the Primary Survey. Therefore, hospital in general and emergency installations in particular are expected to conduct training, woekshop and seminars to improve the skills and knowledge of nursing in handling of critical nursing emergency.